Hormonal changes in persons with chronic generalized periodontitis - O. A. Uspenskaya; S. A. Spiridonova; E. A. Shevchenko; G. A. A. Davtyan (Эндодонтия Today)
Relevance. Recently, there is a tendency to increase the prevalence of chronic generalized periodontitis. It is established that one of the important factors predisposing to the development of generalized periodontitis and influencing its course is systemic osteoporosis, in the development of which the status of hormones regulating mineral metabolism is of great importance. In this regard, it is important to study the hormonal status of patients with aggressive forms of periodontitis to identify the main causal factors of the disease and their elimination.Aim. Study of changes in the hormonal status of persons with chronic generalized periodontitis. Materials and metods. A total of 100 patients aged 26 to 35 years diagnosed with chronic generalized periodontitis moderate and severe. Depending on the treatment, all the examined patients were divided into 4 groups: in group 1 were used calcemine and locally – metronidazole ; in group 2 were used calcemine and locally – metronidazole and EPLAN; in group 3 were used Tevabone and locally – metronidazole; in group 4 were used Tevabone and locally – metronidazole and EPLAN. To determine the level of calcidiol in serum, the test "ARCHITECT 25-OH Vitamin D" was used, the level of calcitonin was determined using The biomerica Calcitonin test (Biomerica Calcitonin, determination of intact parathyroid hormone in serum and plasma of human blood was carried out using the test system "Elecsys PTH". Data processing was performed using the statistical package STADIA, as well as statistical package add-in Microsoft Excel (2010).Results. There was a decrease in calcidiol and calcitonin, an increase in parathyroid hormone in CGP. The proposed treatment regimen led to the normalization of the studied parameters. Aggressive forms of periodontitis are accompanied by a decrease in calcidiol and calcitonin, an increase in parathyroid hormone in the blood. Conclusions. Clinical improvement and normalization of hormonal background against the background of the use of drugs "EPLAN" and "Tevabon" in the scheme of complex etiopathogenetic treatment was also noted.